Aqueous SET-LRP catalyzed with "in situ" generated Cu(0) demonstrates surface mediated activation and bimolecular termination. Issue 11 (21st March 2015) - Samanta, Shampa R.; Nikolaou, Vasiliki; Keller, Shauni; Monteiro, Michael J.; Wilson, Daniela A.; Haddleton, David M.; Percec, Virgil
<x xml:space="preserve">Abstract</x> Ultrafast, inversely temperature dependent aqueous SET-LRP with "in situ" generated Cu(0) yields quantitative chain-ends demonstrating surface mediated activation and termination.